GUIDELINES FOR USING NAM DOKMAI MANGO TO PROMOTE CAREERS AND GENERATE SUSTAINABLE INCOME OF BAN SANGTAWAN COMMUNITY OF PETCHCHOMPOO SUBDISTRICT AT KOSAMPHI DISTRICT IN KAMPHAENG PHET PROVINCE - Keangkason, Sirinpron; Prasomthong, Pradit; Poomarinpong, Rattapon (Journal of MCU Phetchaburi Review, 2025)
This research employed a participatory action research methodology with two main objectives: (1) to explore sustainable approaches for utilizing Nam Dok Mai mangoes as a foundation for income generation within the community, and (2) to promote the processing and product development of Nam Dok Mai mangoes for the Sangtawan community in Phetchomphu Sub-district, Kosamphi Nakhon District, Kamphaeng Phet Province. Key informants included the village head and the leader of the Sangtawan Women’s Occupational Group. The target groups were divided into: (1) a qualitative research group consisting of five representatives from the women’s occupational group and relevant stakeholders, and (2) a participatory action research group involving 20 members of the community’s women’s group who participated in hands-on product development training. Data were collected through in-depth interviews, focus group discussions, brainstorming sessions, and questionnaires. The data were analyzed using descriptive statistics including percentage, mean, and standard deviation, as well as inductive reasoning. The research findings revealed that: (1) The potential for utilizing Nam Dok Mai mangoes as a sustainable income-generating resource was identified through the production of dried mango sheets. The analysis of community capacity and participation indicated a strong demand for aesthetically appealing and unique products, along with an interest in online sales channels. There was a clear need for training in product design and digital marketing. (2) The promotion of mango sheet processing for the community was carried out through capacity building and product development. Brainstorming sessions and hands-on product development training were organized to help the interested group of housewives in Ban Saeng Tawan community create distinctive, convenient-to-consume products with unique identities. The research team and guest experts provided knowledge and guidance, enabling participants to implement and continue the process independently. The project also included the co-creation of product logos, labels, and attractive packaging, as well as training on online marketing strategies to increase income. In addition, business planning and distribution strategies were developed collaboratively. Upon completion of the project, follow-up assessments showed that the production and distribution of mango sheets by the housewives’ group in Ban Saeng Tawan community was successful. The initiative led to continuous production, significantly increased income through expanded online sales channels, and ultimately enhanced the quality of life and sustainable self-reliance of the community.